Techniques and a Model for the Incorporation of Indigenous Knowledge Systems Into the Natural Science Curriculum in Schools - Benkosi Madlela (Studies in Learning and Teaching, 2024)
The study explored the techniques and a model that could be used to incorporate Indigenous Knowledge Systems (IKS) into the Natural Science (NS) curriculum. An interpretivist research philosophy and a qualitative research approach guided the collection of in-depth data from participants in their natural settings in schools. Data was collected from Headmasters through face-to-face interviews using an interview guide, and from NS Heads of Departments (HODs) and NS teachers through a focus group discussion guide. In each of the five selected schools in Pongola, three NS teachers, one Headmaster and one NS HOD participated in the study. This gave a total of twenty-five participants. Findings revealed that though NS Curriculum and Policy Statements (CAPS) 2012 curriculum documents instructs teachers to use IKS in class, these documents do not state which IKS content should be taught. Discretion is left to individual teachers. This poses challenges to teachers as IKS differ across different cultures in the country, and schools did not have IKS study material for teachers and learners. The study recommended that the Department of Basic Education should review its policy and clearly state the content of IKS that should be taught in NS, broaden the scope of parental involvement to include participation in IKS topics and activities, develop a standardised IKS knowledge strand, involve researchers and publishers to produce IKS study material, and adopt the Madlela model as a guiding Framework to incorporate IKS into the NS curriculum as a full knowledge strand.